Perylene bisimide solar cell electron transport layer material and preparation method thereof

By introducing phenyl sulfoxide side chains into perylene imide-based electron transport layer materials, the molecular stacking behavior is improved, the problem of excessive aggregation and crystallization is solved, the film-forming properties and electron transport efficiency are enhanced, and a highly efficient photoelectric conversion effect is achieved.

CN120904200APending Publication Date: 2025-11-07TAIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511252344.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-03
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

In existing organic solar cells, perylene imide electron transport layer materials are prone to excessive aggregation and crystallization, which affects film formation and electron transport efficiency.

Method used

By introducing benzene and its specific substituents into the core framework of perylene-imide electron transport layer materials, the molecular stacking behavior is improved and the interaction between molecules is enhanced, thus preparing perylene-imide electron transport layer materials with phenyl sulfoxide side chains.

Benefits of technology

The electron transport layer's film-forming properties and electron transport efficiency were improved, thereby enhancing the photoelectric conversion efficiency of solar cells to reach or exceed 19%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120904200A_ABST
    Figure CN120904200A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic photoelectric materials, and particularly relates to a perylene bisimide solar cell electron transport layer material and a preparation method thereof. The chemical structural general formula of the material is shown as a formula A, wherein an Ar group can be selected from any structure shown as a formula B; the phenyl sulfoxide-containing perylene bisimide electron transport layer material developed by the invention has good alcohol solubility, stability and photoelectric properties. The invention provides a simple, convenient and efficient synthetic route for the structural design of the electron transport layer material of the organic solar cell, and has potential application value in organic solar cells and related photovoltaic fields.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of organic optoelectronic materials, and particularly relates to a perylene diimide solar cell electron transport layer material and a preparation method thereof. BACKGROUND

[0002] Since the 21st century, organic photovoltaics have attracted much attention due to their advantages such as light weight, low cost manufacturing and wide band light absorption, and meet the trend of developing new renewable energy. In recent years, great progress has been made in the research of organic solar cells, and the device efficiency has increased from 1% in the early stage to nearly 21%, and a breakthrough of 21% has been reported. Organic solar cells mainly use organic materials with photosensitive properties as semiconductor materials to generate voltage and current through photovoltaic effect. The working principle of organic solar cells is similar to that of inorganic solar cells, which is based on photovoltaic effect. The basic structure of organic photovoltaics includes an active layer, an interface layer and an electrode material. The electron transport layer material is between the active layer and the metal electrode. A good electron transport layer material can effectively improve the charge injection performance, reduce the interface resistance, avoid the loss of charges and improve the stability of the battery. At present, the common electron transport layer material usually takes perylene diimide (PDI) as the core skeleton. This kind of material is widely used due to its excellent electron mobility. However, PDI small molecules often have the problem of excessive aggregation and crystallization, which affects the film-forming property. The perylene diimide electron transport layer material (CILs) of the present application significantly improves the molecular packing behavior by introducing benzene and its specific substituent groups at the bay position of the core skeleton. The PDI skeleton introduces a large planar benzene ring, which not only increases the steric hindrance and inhibits the excessive packing of the core skeleton, but also enhances the ordered packing of the side groups. At the same time, the polarity of the substituent group enhances the interaction between the molecules, further regulating the packing state of the molecules. This structure design not only optimizes the film-forming property, but also improves the electron transport efficiency of the material, so as to realize more efficient electron transport in the electron transport layer. The photoelectric conversion efficiency of the solar energy device using the electron transport layer reaches or breaks through 19%. SUMMARY

[0003] In view of the problems existing in the prior art of organic solar cells, the present application aims to provide a perylene diimide solar cell electron transport layer material and a preparation method thereof. The perylene diimide electron transport layer material containing benzyl sulfoxide side chains has excellent electrochemical performance and film-forming property, which can not only improve the photoelectric conversion efficiency of the solar cell, but also has good solution processability, providing a high-performance electron transport layer material for improving the efficiency of organic solar cells.

[0004] In the first aspect of the present application, a perylene diimide solar cell electron transport layer material is provided, and the structural formula is shown as formula A:

[0005]

[0006] wherein Ar is any one of the following formula B structures:

[0007]

[0008] Optionally, the side chain phenyl sulfoxide-containing perylene imide electron transport layer material has the following molecular structure:

[0009]

[0010] The second aspect of the present application provides a photovoltaic device containing the phenyl sulfoxide-containing side chain perylene imide electron transport layer material of the first aspect.

[0011] Optionally, the photovoltaic device structure comprises, in sequence, a substrate, an anode interface layer, an active layer, an electron transport layer and a metal electrode.

[0012] Optionally, the substrate comprises transparent glass and transparent conductive film.

[0013] Optionally, the anode interface layer is selected from any one of PEDOT:PSS and MoO3.

[0014] Optionally, the electron transport layer is selected from any one of PDIN-p-MPSO and PDIN-m-MPSO.

[0015] Optionally, the thickness of the anode interface layer is 20-50 nm.

[0016] Optionally, the thickness of the electron transport layer is 5-15 nm.

[0017] Optionally, the thickness of the active layer is 80-150 nm.

[0018] Optionally, the metal electrode is selected from any one of silver and aluminum.

[0019] Optionally, the photovoltaic device is a polymer solar cell.

[0020] Here, the polymer solar cell refers to a polymer as the donor and a small molecule as the acceptor in the active layer.

[0021] In a third aspect of the present application, a preparation method of the phenylsulfoxide side chain-containing perylene diimide electron transport layer material is provided, comprising mixing raw materials and reacting to obtain the phenylsulfoxide side chain-containing perylene diimide electron transport layer material, wherein the raw materials comprise 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride, 3-dimethylaminopropylamine, and sulfoxide phenylboronic acid ester, and the molecular structure of the phenylsulfoxide side chain-containing perylene diimide electron transport layer material is shown in the following formula A:

[0022]

[0023] wherein Ar is any one of the following formula B structure:

[0024]

[0025] Optionally, R in the molecular structure of the phenylsulfoxide side chain-containing perylene diimide electron transport layer material can be any one of the following structures:

[0026]

[0027] Optionally, the preparation method of the phenylsulfoxide side chain-containing perylene diimide electron transport layer material comprises the following steps:

[0028] (1) 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride and 3-dimethylaminopropylamine are added to a reaction solvent, and after reaction, the structure of PDI-2Br is shown in formula II;

[0029] (2) PDI-2Br, sulfoxide phenylboronic acid ester, a solvent, and a catalyst are mixed, and the reaction can obtain the electron transport layer material;

[0030] The reaction route is shown as follows:

[0031]

[0032] Optionally, in the step (1), the molar ratio of 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride to 3-dimethylaminopropylamine is 1:2-1:6;

[0033] Optionally, in the step (1), the solvent is at least one selected from the group consisting of n-butanol, acetic acid, and toluene;

[0034] Optionally, in the step (1), the reaction temperature is 80-100°C, and the reaction time is 10-24h;

[0035] Optionally, in the step (1), after the reaction, the system is cooled to room temperature, poured into water, and then 4N sodium hydroxide solution is added to adjust the pH to 7-9, dichloromethane is extracted, the organic phase is concentrated, and then column chromatography (the column is filled with 300-400 mesh silica gel, and dichloromethane and methanol with a volume ratio of 20:1 are used as eluent) is used for purification, and finally the product PDI-2Br is obtained by drying and concentrating;

[0036] In the step (2), the molar ratio of NDI-2Br to phenylsulfoxide borate is 1:2-1:6.

[0037] Optionally, in the step (2), the solvent is at least one selected from toluene, xylene, and 1,4-dioxane.

[0038] Optionally, in the step (2), the catalyst is at least one selected from tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium, and 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride.

[0039] Optionally, in the step (2), the reaction temperature is 100-120 DEG C, and the reaction time is 8-10 h.

[0040] In the step (2), after the reaction, the system is cooled to room temperature, the solvent is evaporated under reduced pressure, and the electronic transport layer material is obtained by silica gel column chromatography.

[0041] The specific embodiments of the present application have the following beneficial effects:

[0042] The present application takes perylene imide as the core structure, and a product with good alcohol solubility is synthesized by Suzuki coupling reaction, which provides guarantee for the core application of the product as the electronic transport layer material of the solar cell. At the same time, the visible light absorption range of the perylene imide structure can be well complementary to the active layer of the solar cell, as the material can improve the LUMO energy level of the electronic transport layer, further improve the open circuit voltage and short circuit current density of the device, and finally realize high photoelectric conversion efficiency. BRIEF DESCRIPTION OF DRAWINGS

[0043] The drawings accompanying the specification of the present application form a part of the present application and serve to provide further understanding of the present application, and the illustrative embodiments of the present application and their descriptions serve to explain the present application, and do not constitute improper limitations on the present application.

[0044] Figure 1 J-V curve of Example 3;

[0045] Figure 2 J-V curve of Example 4;

[0046] Figure 3 J-V curve of Example 5;

[0047] Figure 4 The nuclear magnetic resonance hydrogen spectrum of PDI-2Br in Example 1 of the present application;

[0048] Figure 5 The nuclear magnetic resonance hydrogen spectrum of Example 1 of the present application;

[0049] Figure 6 The nuclear magnetic resonance hydrogen spectrum of Example 2 of the present application; Detailed implementation method

[0050] The following descriptions are all exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as commonly understood by those skilled in the art to which the present application belongs. The reagents used in the present examples are not marked with the manufacturer, and are all conventional products that can be purchased on the market.

[0051] Example 1:

[0052] 1. Synthesis of PDI-2Br compound, the synthesis method is as shown below:

[0053] The specific steps are:

[0054] 1g (1.81mmol) of 5,12-dibromoanthracene [2,1,9-def:6,5,10-d'e'f'] diisopentene-1,3,8,10-tetraone was dissolved in n-butanol, heated to 90°C under N2, 23mL (18.1mmol) of 3-dimethylaminopropylamine was added after 15min of reaction, kept at 90°C for 24h, after the reaction was completed, it was lowered to room temperature, water was introduced to precipitate the solid, suction filtration, the filter cake was washed with ethanol to obtain a red solid.

[0055] The structure of the target product prepared was characterized, and the specific steps were as follows: 400M Hz, CDCl3, 1 HNMR: δ 9.46 (d, J = 8 Hz, 2H), δ 8.88 (s, 2H), δ 8.68 (d, J = 8 Hz, 2H), δ 4.30-4.23 (m, 4H), δ 2.48 (t, J = 8 Hz, 4H), δ 2.26 (s, 12H), δ 1.97-1.90 (m, 4H). As shown in the following figure: Figure 3

[0056] 2. Synthesis of perylene imide derivative PDIN-p-MPSO, the synthesis reaction formula is as shown below:

[0057]

[0058] The specific synthesis steps are:​

[0059] PDI-2Br (0.144 g, 0.2 mmol), 4-(methylsulfinyl)benzeneboronic acid pinacol ester (0.168 g, 0.6 mmol), potassium carbonate (0.55 g, 4 mmol) and catalyst Pd(PPh3)4(0.012 g, 0.01 mmol) were dissolved in a mixed solvent of toluene, ethanol and water, in which the volume ratio of toluene:ethanol:water was (4:2:1), and reacted at 100°C for 8h or more under N2protection. After cooling to room temperature, extraction was performed three times using chloroform, and the organic solvent was removed under reduced pressure. After washing and drying, purification was performed on a silica gel plate using chloroform / methanol=2:1 to obtain the final product.

[0060] The structure of the target product prepared was characterized as follows: 400 MHz, CDCl3, 1 HNMR: δ 8.48 (s, 2H), δ 8.15 (d, J=8 Hz, 2H), δ 7.91-7.66 (m, 8H), δ 7.63 (d, J=8 Hz, 2H), δ 4.26 (t, J=8 Hz, 4H), δ 2.87 (s, 6H), δ 2.50 (t, J=8 Hz, 4H), δ

[0061] 2.31 (s, 12H), δ 1.99-1.90 (m, 4H). As shown in the Figure 4

[0062] Example 2:

[0063] The synthesis of the derivative PDIN-m-MPSO of perylene bisimide is shown in the following reaction scheme:

[0064]

[0065] The specific steps are as follows:

[0066] PDI-2Br (0.144 g, 0.2 mmol), 3-(methylsulfinyl)benzeneboronic acid pinacol ester (0.160 g, 0.6 mmol), potassium carbonate (0.55 g, 4 mmol) and catalyst Pd(PPh3)4(0.012 g, 0.01 mmol) were dissolved in a mixed solvent of toluene, ethanol and water, in which the volume ratio of toluene:ethanol:water was (4:2:1), and reacted at 100°C for 8h or more under N2protection. After cooling to room temperature, extraction was performed three times using chloroform, and the organic solvent was removed under reduced pressure. After washing and drying, purification was performed on a silica gel plate using chloroform / methanol=2:1 to obtain the final product.

[0067] The structure of the target product prepared was characterized as follows: 400 MHz, CDCl3, 1 ​HNMR: δ 8.53 (s, 2H), δ 8.13 (d, J = 8 Hz, 2H), δ 7.91-7.65 (m, 10H), δ 4.23 (t, J = 8 Hz, 4H), δ 2.73 (s, 6H), δ 2.42 (t, J = 8 Hz, 4H), δ 2.24 (s, 12H), δ 1.99-1.90 (m, 4H). As shown in the attached Figure 5

[0068] Example 3:

[0069] Organic solar cell device using perylene diimide derivative PDIN-p-MPSO as electron transport layer material;

[0070] The preparation of the conventional structure of the D-A heterojunction commonly used in organic solar cells, the donor material PM6, the acceptor material L8-BO, the additive DIB, and the hole transport layer using 2PACz or PEDOT:PSS are included. The structural formulas of the donor PM6 and the acceptor LB-BO are as follows Figure 3

[0071] The specific steps are as follows:

[0072] (1) The ITO glass was cleaned with cleaning agent, deionized water, acetone, and isopropanol for 10 min each, and then dried. After that, the ITO glass was placed in a UV-ozone cleaning machine for 20 min. All subsequent steps were carried out in a glove box.

[0073] (2) DIB was used as an additive and dissolved in chloroform. The chloroform solvent obtained by dissolving DIB was added to PM6 and L8-BO with a mass ratio of 1:1.2. A mixed solution of DIB and the active layer was obtained, and the total concentration of the active layer material in the mixed solution was 15 mg / ml.

[0074] (3) Static coating of the hole transport layer: A PEDOT:PSS aqueous solution was spin-coated on the ITO glass at a speed of 3000 rpm, and then annealed at 100°C in air for 10 minutes.

[0075] (4) Dynamic coating of the active layer: The mixed solution was spin-coated on the surface of the hole transport layer at a speed of 3000 rpm, and then heat annealed at 100°C for 10 min to obtain the active layer.

[0076] (5) Dynamic coating of the electron transport layer: The product PDIN-p-MPSO prepared in Example 1 was dissolved in methanol at a concentration of 1.5 mg / ml, and then the solution was spin-coated on the active layer at a speed of 3000 rpm to obtain the electron transport layer.

[0077] ​​(6) Vacuum deposition of metal cathode: 100 nm Ag was deposited as cathode by vacuum deposition system, and the effective area of the device was 0.04 cm 2 The parameters of the device were measured and shown in Table 1.

[0078] Table 1: The photoelectric performance of the OSCs based on PDIN-p-MPSO electron transport layer in PM6:L8-BO system

[0079]

[0080] Example 4:

[0081] Perylene diimide derivative PDIN-m-MPSO as electron transport layer material of organic solar cell device;

[0082] The specific steps are as follows:

[0083] (1) The ITO glass was cleaned with cleaning agent, deionized water, acetone and isopropanol for 10 min respectively, and then dried. After that, the ITO glass was placed in the ultraviolet-ozone cleaning machine for 20 min. The following steps were carried out in the glove box.

[0084] (2) DIB was used as an additive and dissolved in chloroform. The chloroform solvent obtained by dissolving DIB was added to PM6 and L8-BO with a mass ratio of 1:1.2. A mixed solution of DIB and active layer was obtained, and the total concentration of active layer material in the mixed solution was 15 mg / ml.

[0085] (3) Static coating of hole transport layer: The aqueous solution of PEDOT:PSS was spin-coated on the ITO glass at a speed of 3000 rpm, and then annealed at 100°C in air for 10 minutes.

[0086] (4) Dynamic coating of active layer: The mixed solution was spin-coated on the surface of the hole transport layer at a speed of 3000 rpm, and then heat annealed at 100°C for 10 min to obtain the active layer.

[0087] (5) Dynamic coating of electron transport layer: The product PDIN-m-MPSO prepared in Example 2 was dissolved in methanol at a concentration of 1.5 mg / ml, and then the solution was spin-coated on the active layer at a speed of 3000 rpm to obtain the electron transport layer.

[0088] (6) Vacuum deposition of metal cathode: 100 nm Ag was deposited as cathode by vacuum deposition system, and the effective area of the device was 0.04 cm 2 The parameters of the device were measured and shown in Table 2.

[0089] Table 2: Photovoltaic performance of OSCs based on PDIN-m-MPSO electron transport layer under PM6:L8-BO system

[0090]

[0091] Example 5:

[0092] The comparative example is based on Example 3, except that the spin speed of the electron transport layer is changed to 4000 rpm, and the hole transport layer is changed to 2PACz. The parameters are measured and shown in Table 3:

[0093] Table 3: Photovoltaic performance of OSCs based on PDIN-p-MPSO electron transport layer under PM6:L8-BO system

[0094]

[0095] Further, the voltage (J-V) characteristic curves of each example are shown in the following figures: Figure 1 , Figure 2 , Figure 3 .

Claims

1. A phenylsulfoxide side chain-containing perylene imide solar cell electron transport layer material, characterized in that, The compound has a structural formula as shown in formula A: Wherein, Ar is any one of the following formula B structures:

2. The phenylsulfoxide side chain-containing perylene diimide solar cell electron transport layer material according to claim 1, characterized in that, The molecular structure is shown as follows:

3. The method for preparing perylene imide electron transport layer material containing phenyl sulfoxide side chains according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: (1) adding 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride and 3-dimethylaminopropylamine into a reaction solvent, and obtaining PDI-2Br after reaction, wherein the structural formula of PDI-2Br is shown in formula C; (2) mixing PDI-2Br, sulfoxide phenylborate, a solvent and a catalyst, and obtaining the electron transport layer material after reaction; The reaction route is shown as follows:

4. The production method according to claim 3, wherein The molar ratio of 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride to 3-dimethylaminopropylamine is 1:2-1:6; In the step (1), the solvent is at least one selected from n-butanol, acetic acid and toluene; In the step (1), the reaction temperature is 80-100℃, and the reaction time is 10-24h; In the step (1), after reaction, the system is cooled to room temperature, poured into water, and then 4N sodium hydroxide solution is added to adjust the pH to 7-9, dichloromethane is extracted, the organic phase is concentrated, then column chromatography (300-400 mesh silica gel is filled in the column, and dichloromethane and methanol with a volume ratio of 20:1 are used as eluent) is used for purification, and finally the product PDI-2Br is obtained by drying and concentrating; in the step (2), the molar ratio of NDI-2Br to phenyl sulfoxide borate is 1:2-1:6; In the step (2), the solvent is at least one selected from toluene, xylene and 1,4-dioxane; In the step (2), the catalyst is at least one selected from tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride; In the step (2), the reaction temperature is 100-120℃, and the reaction time is 8-10h; In the step (2), after reaction, the system is cooled to room temperature, the solvent is evaporated from the reaction liquid under reduced pressure, and the electron transport layer material is obtained by silica gel column chromatography.